The long road to Antietam : how the Civil War became a revolution - Slotkin, Richard, 1942- (Liveright Publishing Corporation, 2012)
In the summer of 1862, after a year of protracted fighting, Abraham Lincoln decided on a radical change of strategy, one that abandoned hope for a compromise peace and committed the nation to all-out war. The centerpiece of that new strategy was the Emancipation Proclamation: an unprecedented use of federal power that would revolutionize Southern society.